KOMUNIKASI ORGANISASI DI PERPUSTAKAAN BAPUSIPDA JAWA BARAT - Gumilar, Widy; Cythia, Riche; Silvana, Hana (Edulib, 2014)
ABSTRACT This subject is examined in the study is whether the Organization's communication about to the performance of librarian at BAPUSIPDA in West Java. The purpose of this research is to determine (1) the Organization about the power performance communication library in BAPUSIPDA, West Java, (2) the communication line to the bottom about the performance of librarian in BAPUSIPDA, West Java, (3) the communication line to the top about the performance of librarian at BAPUSIPDA in West Java. The population in the study was BAPUSIPDA in West Java libraries powered by the sample as many as 56 people. Research methods using descriptive method quantitative approach. The results showed Organizational communication in West Java BAPUSIPDA categorized good. Organizational communication in West Java BAPUSIPDA categorized effectively, however we recommend that the library can create a more effective organization communications so that the performance of the library has increased horsepower.Keywords: Organizational Communication, Librarian, Performance  ABSTRAK Tulisan ini bermaksud untuk mengupas komunikasi organisasi yang ada di Badan Perpustakaan dan Arsip Daerah (BAPUSIPDA) Jawa Barat. Tujuan Penelitian ini yaitu untuk mengetahui (1) komunikasi organisasi dilihat dari kinerja tenaga perpustakaan di BAPUSIPDA Jawa Barat, (2) alur komunikasi ke bawah dilihat dari kinerja tenaga perpustakaan di BAPUSIPDA Jawa Barat, (3) alur komunikasi ke atas dilihat dari kinerja tenaga perpustakaan di BAPUSIPDA Jawa Barat. Populasi dalam penelitian adalah tenaga perpustakaan BAPUSIPDA Jawa Barat dengan sampel sebanyak 56 orang. Metode penelitian menggunakan metode deskriptif dengan pendekatan kuantitatif. Hasil penelitian menunjukkan bahwa Komunikasi organisasi di BAPUSIPDA Jawa Barat, berlangsung secara baik.Komunikasi organisasi di BAPUSIPDA Jawa Barat dikategorikan efektif, namun sebaiknya perpustakaan dapat menciptakan komunikasi organisasi yang lebih efektif agar kinerja tenaga perpustakaan semakin meningkat.Kata Kunci: Komunikasi Organisasi, Tenaga Perpustakaan, Kinerja